KEMITRAAN SEKOLAH DAN ORANG TUA DALAM PENANAMAN KEDISPLINAN IBADAH SISWA SMA NEGERI 5 YOGYAKARTA - Nurfiyani Dwi Pratiwi (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2016)
Nurfiyani Dwi Pratiwi. Partnership Schools And Parents In Students’ Worship Disciplines Education.Yogyakarta: Islamic Teaching Department ofTarbiya and Teaching Faculty UIN Sunan KalijagaYogyakarta. This study aims to determine the form of partnership schools and parents in educateworship discipline of students, as well as factors supporting and inhibiting. This is a qualitativeresearch using approach of Sociology.The results of this research show that 1) Forms of partnerships: teachers and parents meetings,correspondence the school and parents, home visits, parent involvement in school events, associationsof parents and teachers, and periodic reports using a books report. 2) The supporting factors: the socialcompetence of teachers, parents’ attention in children’s education, and open access schools. Inhibitingfactors: level of education and the work of parents and teachers administrative tasks.Keywords: Partnership, School, Parent, and Worship.